2022
DOI: 10.1093/brain/awac300
|View full text |Cite
|
Sign up to set email alerts
|

Source-sink connectivity: a novel interictal EEG marker for seizure localization

Abstract: Over 15 million epilepsy patients worldwide have drug-resistant epilepsy. Successful surgery is a standard of care treatment but can only be achieved through complete resection or disconnection of the epileptogenic zone, the brain region(s) where seizures originate. Surgical success rates vary between 20% and 80%, because no clinically validated biological markers of the epileptogenic zone exist. Localizing the epileptogenic zone is a costly and time-consuming process, which often requires days to weeks of int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 114 publications
2
16
0
Order By: Relevance
“…Our findings here did not depend on the presence of iEEG data, and even iEEG data were available we only included a low-resolution description of them. IEEG data does provide the most detailed information of epileptogenic activity, and is it often the most valuable tool to identify the epileptogenic zone or predict surginal outcome for patients with complicated ethiology [22,25,27,[33][34][35][36]. In fact, for the modeling cohort we found the best classification results using the goodness-of-fit of the ESSES-predicted seizure propagation patterns to the iEEG seizures, in agreement with previous studies [27].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings here did not depend on the presence of iEEG data, and even iEEG data were available we only included a low-resolution description of them. IEEG data does provide the most detailed information of epileptogenic activity, and is it often the most valuable tool to identify the epileptogenic zone or predict surginal outcome for patients with complicated ethiology [22,25,27,[33][34][35][36]. In fact, for the modeling cohort we found the best classification results using the goodness-of-fit of the ESSES-predicted seizure propagation patterns to the iEEG seizures, in agreement with previous studies [27].…”
Section: Discussionsupporting
confidence: 90%
“…Importantly, the global parameters of ESSES were defined at the population level, and the model was individualized for each patient via patient-specific MEG networks, which characterized the local spreading probabilities. As a consequence, ESSES can be extended to patients without iEEG recordings, in contrast to previous modeling studies, which typically required the existence of patient-specific iEEG data to individualize the model for each patient [22,25,27,[33][34][35][36]. IEEG allows for a highly resolved description of seizure dynamics, but its spatial sampling is sparse and it is highly invasive.…”
Section: Introductionmentioning
confidence: 99%
“… 70 , 71 Our findings may also be considered in the context of patient-specific dynamical network models based on the principle of ‘sources’ and ‘sinks’. 72 Future studies may estimate source–sink metrics from VSs time series extracted non-invasively from HD-EEG and MEG data to also validate their role as a non-invasive interictal biomarker of the EZ. Finally, our tool has the ability to reconstruct brain signals with similar FC features with those obtained invasively through iEEG.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Interictal Suppression Hypothesis, seizures are prevented during interictal activity by successful inhibition of the epileptogenic zone (EZ) (Johnson et al, 2023). To this regard, it was shown that regions belonging to the EZ were indeed those with the highest inward connections (sinks) (Gunnarsdottir et al, 2021; Johnson et al, 2023), likely reflecting inhibitory inputs from regions external to the EZ, that could be replaced by outward connections supporting seizure spread once the seizure begins (Narasimhan et al, 2020). High functional segregation of the EZ was also shown at rest (Bandt et al, 2014; Johnson et al, 2023; Schevon et al, 2012).…”
Section: Discussionmentioning
confidence: 99%